Analisis Tindak Tutur Ekspresif dalam Novel Home Sweet Loan Karya Almira Bastari - MAYASARI, DEVI; SUSILAWATI, LIS; MULIYONO, NURWAKHID (Universitas Insan Budi Utomo, 2024)
This research examines the analysis of expressive speech acts in the novel Home Sweet Loan by Almira Bastari. The problems discussed in this research: (1) What are the types of expressive speech acts in the novel Home Sweet Loan by Almira Bastari? (2) What is the function of expressive speech acts in the novel Home Sweet Loan by Almira Bastari? The objectives of this research: (1). Describe the types of expressive speech acts in the novel Home Sweet Loan by Almira Bastari (2). Describe the function of expressive speech acts in the novel Home Sweet Loan by Almira Bastari. This research is included in the type of qualitative descriptive research because the data collected is in the form of words. The data and data sources for this research are expressive utterances contained in the novel Home Sweet Loan by Almira Bastari. The data collection technique used in this research is the listening and note-taking method. The data analysis technique in this research was carried out by observing followed by describing the problem with the data. Based on data analysis in the novel Home Sweet Loan by Almira Bastari, the form and function of 20 types of expressive speech acts were found, including the speech acts of agreeing, praising, apologizing, saying thank you, expressing shame, complaining, protesting, sarcastic, expressing desire, expressing surprise, expressing disagreement, expressing pity.